2015
DOI: 10.1177/1756287215614236
|View full text |Cite|
|
Sign up to set email alerts
|

Pazopanib in the treatment of advanced renal cell carcinoma

Abstract: Pazopanib is an orally available multitargeted tyrosine kinase inhibitor (a class of targeted therapies) that inhibits tumor angiogenesis and cell proliferation. The safety and efficacy of pazopanib (noninferior to sunitinib for progression-free survival) in patients with advanced or metastatic renal cell carcinoma (mRCC) have been demonstrated in several clinical trials. However, in addition to therapeutic efficacy, treatment choices should also take into account health-related quality of life (HRQoL) aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In second-line trials of sunitinib in aRCC (post VEGF-targeted therapy), reported ORRs have ranged from 15 to 27%, and median PFS has ranged from ~ 5–18 months [ 14 ]. The TKI pazopanib has also demonstrated efficacy in treating first- and second-line aRCC [ 15 ]. In a phase III study (VEG105192) of pazopanib versus placebo in treatment-naïve or pretreated patients ( N = 435), median PFS was 9.2 versus 4.2 months ( P < 0.0001), and ORR was 30% versus 3% ( P < 0.001) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In second-line trials of sunitinib in aRCC (post VEGF-targeted therapy), reported ORRs have ranged from 15 to 27%, and median PFS has ranged from ~ 5–18 months [ 14 ]. The TKI pazopanib has also demonstrated efficacy in treating first- and second-line aRCC [ 15 ]. In a phase III study (VEG105192) of pazopanib versus placebo in treatment-naïve or pretreated patients ( N = 435), median PFS was 9.2 versus 4.2 months ( P < 0.0001), and ORR was 30% versus 3% ( P < 0.001) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,1719 In patients receiving first-line therapy with pazopanib, or second-line and subsequent therapy with axitinib, sorafenib, pazopanib, and everolimus, HRQoL was maintained but not improved when compared with placebo. 3,5,18,20 In the CheckMate 025 trial, the deterioration in HRQoL in patients treated with everolimus may reflect toxicities associated with this agent. 21 Consequently, the improvements in HRQoL with nivolumab treatment compared with everolimus treatment in the CheckMate 025 trial are particularly noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Anti-angiogenic and mTOR-targeted agents have changed the therapeutic landscape for advanced or metastatic RCC (aRCC), but these treatments are associated with limited overall survival (OS), toxicities related to their specific mechanisms of action, and limited improvement in health-related quality of life (HRQoL) for this patient population. 1,35 …”
Section: Introductionmentioning
confidence: 99%
“…This evidence is consistent with that obtained in a retrospective comparative study [ 25 , 26 ] (Table 2 ) and also in the real-life retrospective SPAZO study [ 25 , 26 ] which showed a PFS of 11.1 months. Other studies have reported PFS rates of between 10.5 and 14.1 months [ 19 , 27 29 ].…”
Section: Resultsmentioning
confidence: 99%